The Influence of Leadership on The Level of Discipline and Performance of Assistant Investigators at The Central Java Regional Police Criminal Investigation Unit - Dwi Hatmoko, Bondan; Yolanda, Yolanda; Astuty, Pudji (Journal Research of Social Science, Economics, and Management, 2023)
A pioneer is somebody who leads by starting social way of behaving by making due, coordinating, putting together, or controlling the endeavors/endeavors of others or through eminence, power, or position. The focus of power leaders is on their success in influencing others to produce an impact. It is believed that the success of a leader moves and influences others through his power toward the good of the other people and the organization he leads. In complex social situations, cooperation and collaboration are needed to build great work. In such situations, leaders and leadership are always needed for effectiveness and efficiency. Leadership emerged with human civilization, where they gathered to maintain their existence, challenging the beasts and the natural surroundings. There has been cooperation between humans and an element of leadership. Thus, it can be concluded that leaders and leadership wherever and whenever they are always needed, especially in modern times now and in the future. The article attempts to investigate the connection among authority and the degree of discipline and execution of collaborator examiners at the Focal Java Territorial Police’s Criminal Examination Unit.